Robust hydraulic actuator force control through relief discharge. (April 2015) - Nourizadeh, Reza; Rezaei, S Mehdi; Zareinejad, Mohammad; Baghestan, Keivan; Tivay, Ali; Saadat, Mozafar
Actuator force control in servo-hydraulic systems has numerous applications in machinery and industrial settings. The prevalent hydraulic configuration for force control utilizes a proportional directional control valve to properly route the supplied hydraulic fluid toward the chambers of the actuator. It is well known that this configuration imposes certain physical limitations on force-tracking performance. In this article, a different configuration is utilized to improve the hydraulic force control performance. This is done by replacing the proportional directional control valve with a proportional double-stage relief valve. It is shown that this new setting is superior in its achievable force-tracking performance. This comes at the cost of a more challenging control problem compared to the proportional directional control valve case, due to the presence of un-modeled dynamics and unknown parameters. A robustH ∞ control approach has been followed as the main solution to address uncertainty problems. However, conservative robust design imposes its own limitations on force-tracking performance. To address this issue, a combination of additional switched-proportional–integral–derivative and Prandtl–Ishlinskii hysteresis compensation control loops is proposed. Conditions are derived under which the additional loops improve the performance of the robustH ∞ controller. The effectiveness of the proposed configuration and control method is demonstrated by the experimental results.